Quality of work life, selected socio-demographic profile and job performance of nursing faculty in state universities in Region IV-A - De Vera, Lenila A.
The study aimed to find a correlation between the Quality of Work Life (QWL), selected socio-demographic profile and the job performance of the nursing faculty in various state universities in Region IV-A. It utilized a non-experimental descriptive-correlational research design. The data for the study was analyzed using multiple statistical procedures: mean standard deviation, Spearman's rank- order correlation rho, Chi-square test and Pearson r. Simultaneous Multiple Regression was used to determine the predictors of Job Performance among Quality of Life Indicators.